Encyclopedia of literary translation into English - Classe, Olive (London. : Fitzroy Dearborn Publishers, 2000)
Inlcudes articles about translations of the works of specific authors and also more general topics pertaining to literary translation
v. 1. A - L -- v. 2. M - Z
Keywords: Translating and interpreting -- Encyclopedias; Literature -- Translatiions into English -- Encyclopedias